Exceptional stability of hydrotalcite derived spinel Mg(Ni)Al2O4 catalyst for dry reforming of methane - Abbas, Muzafar; Sikander, Umair; Mehran, Muhammad Taqi; Kim, Sang Hoon (Elsevier BV, 2022)
Development of methane dry reforming catalyst is very important for economical production of syngas from CH4 and CO2 and reduction of greenhouse gases. Ni-based hydrotalcite derived spinel catalysts were synthesized for dry reforming of methane (DRM). Properties of the catalyst such as reducibility, basicity, morphology, texture and crystal structure, had a great impact on catalyst's activity and stability. Superior catalytic activity and stability during DRM process was achieved with the formation of hydrotalcite derived spinel (NiAl2O4) structures, eruption of carbon nanofibers (CNFs) from carbon layer, and formation of Ni0 active sites on the tips of these CNFs. The Ni particles from reduction of NiO and NiAl2O4 evolved on top of the CNFs and provided a strong metal-support interactions resulting in high resistance against sintering and coking at 850 degrees C during the longterm DRM process (200 h).